Factors Affecting Agricultural Insurance Acceptability of Paddy Farmers in East Java, Indonesia - Sujarwo Sujarwo; Sapto Mei Novita Rukmi (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Risk and uncertainty in rice farming create more possibility for farmers to lose their profit, which results in the vulnerability of continuing their farming. As noted, rice is the main staple food for Indonesian, and it determines the food security significantly. The aims of the study are to identify rice farmers’ acceptance to agricultural insurance, to analyze the factors affecting rice farmers’ acceptability for agricultural insurance, and to estimate rice farmers’ willingness to pay (WTP) for agricultural insurance. The analyses include descriptive statistics depicting the respondents’ characteristics, logistic analysis of the factors affecting the acceptance of agricultural insurance, and the farmers’ willingness to pay premium regarding the government program of agricultural insurance for rice farmers. The results show that 80% of the randomly-selected 50 farmer respondents accept the agricultural insurance. The positive factors affecting the acceptance of agricultural insurance are experience in rice farming and income from rice farming. Other factors considered in the logistic model are not statistically significant. Those factors are farmers’ age, education, income from rice farming, experience of rice farming, land size of rice production, the family size, and the experience of accessing any other previous insurance. Additionally, the rice farmers’ willingness to pay the premium of agricultural insurance on average is IDR35,113 per hectare. This amount is obtained from the 40 respondents who accept the agricultural insurance program from the government.Keywords: agricultural insurance, premium, willingness to pay, logistic analysis, descriptive statistics